Teaching Lab Science Courses Online : Resources for Best Practices, Tools, and Technology - Jeschofnig, Linda, 1948-; Jeschofnig, Peter (San Francisco, CA : Jossey-Bass, 2011)
'Teaching Lab Science Courses Online is a practical resource for educators developing and teaching fully online lab science courses. First, it provides guidance for using learning management systems and other web 2.0 technologies such as video presentations, discussion boards, Google apps, Skype, video/web conferencing, and social media networking. Moreover, it offers advice for giving students the hands-on'wet laboratory' experience they need to learn science effectively, including the implications of implementing various lab experiences such as computer simulations, kitchen labs, and commercially assembled at-home lab kits. Finally, the book reveals how to get administrative and faculty buy-in for teaching science online and shows how to negotiate internal politics and assess the budget implications of online science instruction'--
Includes bibliographical references (pages 163-167) and index.
Keywords: Science -- Study and teaching (Higher); Laboratories; Web-based instruction -- Design; Science -- Electronic information resources; EDUCATION / Higher